Innovation as an Adaptive Response to Natural Disasters : a Dynamic Cross-Country Panel Data Analysis of the Impact of Floods on Risk-mitigating Patents - From, Emma (SLU/Dept. of Economics, 2022)
As climate change is increasing the intensity and frequency of natural disasters worldwide, the question of coping with extreme events is gaining more attention. Within the climate discourse, innovation is an essential adaptation strategy. This study explores the relationship between natural disasters and risk-mitigating innovation by employing a dynamic cross-country panel data analysis on the impact of social and economic damage from floods on patent applications for flood-mitigating innovation domestically between 1996–2018. Inconsistent with prior literature and the theory of risk perception, the results provide no clear evidence of floods having a spurring effect on patenting activities. The estimated effects are significantly small for all damages, suggesting a weak positive impact on patents from economic damages, while social damage seems to have a slightly dampening effect. The findings contribute to the scarce research on the link between climate shocks and innovation as an endogenous process. Based on the findings of this study, more research is needed to improve the econometric approach and make further use of patent and damage data in order to examine how weather extremes influence proactive measures and adaptive responses.